Teachers’ Understanding of Psycholinguistic and Its Relation to Arabic Teaching Method in Modern Pesantren - Nurhamim, Nurhamim; Indriana, Dina; Yani, Achmad (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
To enhance the quality of language learning, one should be able to deliver the material in the most effective and suitable method. This research aims to determine the relationship between psycholinguistics and learning methods. Psycholinguistics is an applied language science that plays a prominent role in planning language teaching. The implications of psycholinguistics are seen in the teacher's ability to manage teaching with learning methods, curriculum implementation, and selection of teaching materials. Psycholinguistics in the curriculum provides the basics for teachers in formulating objectives for teaching. The method in this research uses a quantitative type of research to determine the relationship between psycholinguistics and language learning methods. The results of the research show that the sig value is 0.000 <0.05, which indicates that there is a positive relationship between psycholinguistics and learning methods.